The Provision of Incentives in Firms - Prendergast, Canice (Journal of Economic Literature, 1999)
This paper provides an overview of the existing theoretical and empirical work on the provision of incentives. It reviews the costs and benefits of many types of pay-for-performance, such as piece rates, promotions, and long-term incentives. The main conclusions are (i) while there is considerable evidence that individuals respond to pay-for-performance, there is less evidence that contracts are designed as predicted by the theory, (ii) there has been little progress made in distinguishing amongst plausible theories, and (iii) we still know little about how incentives are provided to workers whose output is difficult to measure.